Atypical Cerebral Manifestations of Disseminated Mycobacterium tuberculosis - Hwang, Ji Hye; Lee, Kyung Mi; Park, Ji Eun; Kim, Hyug-Gi; Kim, Eui Jong; Choi, Woo Suk; Yang, Na Rae (Frontiers in Neurology, 2017)
Background: We investigated the patterns of cerebral manifestations in patients with underlying pulmonary or extrapulmonary tuberculosis or disseminated tuberculosis. Materials and methods: From January 2010 to September 2016, brain magnetic resonance imaging (MRI) scans were obtained to evaluate cerebral manifestations in patients with underlying pulmonary or extrapulmonary tuberculosis. We also included patients with drug-resistant tuberculosis or disseminated tuberculosis. MRI findings of tuberculous meningitis and tuberculoma were classified as typical; other MRI findings were classified as atypical. Demographic data, risk factors, and drug regimens were collected and analyzed. Results: Twenty-two patients were diagnosed with cerebral tuberculosis. Cerebral tuberculosis was due to hematogenous spread from pulmonary tuberculosis (ten patients), spinal tuberculosis (eight patients), disseminated tuberculosis (three patients), and unknown causes (one patient). There were six patients with typical MRI findings (three patients with typical meningitis involving the basal cistern and supratentorium, one patient with tuberculomas, and two patients with both) and seven patients with atypical MRI findings (five patients with evidence of early meningitis, such as high signal intensity on fluid-attenuated inversion recovery (FLAIR) along the cerebellar folia, and two patients with only hydrocephalus). Conclusions: Besides the typical sites of meningeal involvement, overlooked findings such as FLAIR abnormalities along the cerebellar folia or hydrocephalus should be checked for early detection of cerebral tuberculosis and initiation of the appropriate treatment against disseminated tuberculosis.